Māori student perceptions of group work in their social work degree - Guy, Donna Louise (Groupwork, 2019)
Few practitioners today would argue the value of group work as an effective teaching approach to enhance deep learning opportunities for social work students – but how many of us have stopped towonder whether our students agree? This paper presents the findings from an interpretive study, using a mixed method approach to investigate students’ perceptions of group work. A particular focus was the experiences of Māori students, as one of the frequently cited assumptions about Māori cultural teaching and learning preferences is that they are a communally-minded culture with a preference for group, rather than individualized processes and inquiry. Māori are the indigenous people of Aotearoa New Zealand,comprising 15% of the population. Like many indigenous and colonized cultures, Māori have experienced ongoing oppression and practices of colonization resulting in significant disparities in social, economic status, education, health and wellbeing (Ministry of Health, 2015; Tertiary Education Commission, 2011). Māori are a large client group for social workers, and the profession is keen to ensure a strong Māori presence among the qualified practitioners to work alongside their own people. It is important, then, that teachers give Māori students in higher education every assistance to succeed.The findings from this study highlighted a few surprises. Māori students revealed mixed and, at times, contradictory perceptions of the value of group work. As one participant revealed, “Group work can be really awesome but it can also be really stunting”. While acknowledging a number of benefits, students emphasised peer influences and the role of the teacher as having a significant impact on whether group work was deemed a positive or negative experience. This paper discusses these, and other key themes related to positive and negative group work experiences, along with strategies students suggested to enhance their social work study experience. The paper concludes that generalizing about Māori, and/or possibly other indigenous cultures who naturally thrive in collective environments, does not mean we can assume they will thrive during group work in the higher education classroom. Finally, some reflections and implications for best practice are offered.